In-Hospital Outcomes of Patients Presenting with Acute Anterior STEMI with Right Bundle Branch Block - Zameer, Imran; Kashif, Muhammad; Perveez, Akasha; Murad, Adnara; Asad, Muhammad; Asad, Muhammad; Khan, Aleena; Sana, Ayesha; Hayat, Azmat (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the in-hospital outcomes in Anterior wall ST Elevation Myocardial Infarction patients presenting with Right Bundle Branch Block with different reperfusion strategies. Study Design: Analytical Cross-Sectional Study. Place and Duration of Study: Department of Cardiology, Rawalpindi Institute of Cardiology, Rawalpindi Pakistan, from Sep 2020 to Feb 2021. Methodology: Patients with myocardial infarction who presented to the emergency department of the hospital were included in the study. Further evaluation was performed on individuals with ST elevation in anterior chest leads and new-onset or presumably new Right bundle branch block on electrocardiogram. Anterior wall myocardial infarction was diagnosed based on 4th universal definition of Myocardial infarction. Patients excluded were those with non-anterior ST-elevation myocardial infarction, prior coronary artery bypass grafting, previous percutaneous coronary intervention, or Left bundle branch block.The treatment plan was chosen by the interventional cardiologist. Various parameters were used to measure the outcomes of different therapies. Results: 93 patients were included with 72(77.4%) males and 21 females (22.5%). Mean age was 59.91±11.93 years. Premorbid seen was 41.9% diabetes, 32.3% hypertension, 18.3% smoking. Transient RBBB was seen in 64.5% of the study population and persistence RBBB was 35.5%. Mortality was associated with higher Killip class (p=<0.001), AV block (p=0.078), increased no of coronary vessels involved (p=0.014), increased amplitude of ST elevation (p=0.083) and with lower EF values (p=0.032). Worst outcomes were common in patients on medical treatment. Conclusion: Poor outcomes in Anterior Wall Myocardial Infarction with Right Bundle Branch Block are linked to length of stay, co morbidities, Killip class, amplitude of ST elevation, coronary artery disease complexity and those managed on medical treatment.